KOROH NATIIK MARIA, STUDI HISTORIS TERHADAP AGAMA KRISTEN DALAM DAERAH KEUSIFAN AMARASI ABAD KE - 16 – 17 - Heronimus Bani (Jurnal Lazuardi, 2020)
The religion of Christian has been came in Amarasi. In the beginning, people in Amarasi had ethno-religion called re’u. The Portuguese brought the catholic and Holland brought protestant. When the Holland came in Timor, the Portuguese had been there. Times, both of them wared. In that time Amarasi’s king built a friendship with Portuguese, so the Holland, war not only with the Portuguese but Amarasi too. In the same time the society had been catholic because the influence from the Portuguese. Finally, Amarasi and Portuguese losed in the Penfui war. The king of Amarasi put down the catholic and took up the protestant, because the Holland pushed. So, the society called koroh natiik maria and they drawed in their traditional clothes. Nowadays, the society know the koroh natiik maria is a kind of symbol to their clothes that they called tais. Koroh, is the symbol of the king and kingdom, and maria is the symbol of catholic. This paper used history approach with library study.